Android-Based Learning: Developing Easy with Grammar Application to Learn Grammar - Andi Tenrisanna Syam; Dewi Furwana; Ummul Muhaiminah (FOSTER: Journal of English Language Teaching, 2024)
The writers aimed to develop an application for learning grammar namely Easy with Grammar (EWMAR). The writers applied the Research and Development method by adapting the ADDIE Model, which has five stages: Analysis, Design, Development, Implementation, and Evaluation. 70 learners of the first semester of the Shariah Management Business study program answered a need analysis questionnaire. Sixty-six learners were involved in the field try-out and three experts assessed the writers’ product. The instruments consisted of questionnaires and grammar tests. The technique of data analysis included descriptive qualitative and quantitative. Based on learners' perception questionnaire results, the mean score was 4 (100%), classified as "Excellent," which means that the EWMAR application was appropriate for the eleventh graders of senior high school learners. The average score of experts’ assessments was 3.27, and at the percentile, 81.75% met the "Good" criteria to use it with minor revisions. Therefore, the EWMAR application is feasible as a learning medium. The writers recommended another scholar develop more modern Android-based learning to facilitate the educational process.